The Effect of Teaching Short Stories on Listening Comprehension of Third Grade Libyan Pupils Using Total Physical Response (Journal of Academic Research, 2023)
Total Physical Response (TPR) as a method of teaching young foreign language learners has gained popularity for decades now. A growing number of researches have been conducted in different levels of learning to see its influence on language skills. The aim of this pre-experimental study was carried out in order to test the listening comprehension of third grade Libyan pupils using TPR method. The stories from the prescribed textbook for grade three pupils were used as the subject matter. The participants of this study were 27 third grade primary school pupils of Shuhada Almatar School in Misurata city. The result was analysed using a paired-sample t test which showed that there was a significant difference between the pretest and the posttest results. It was also apparent that the pupils’ participation increased when they were engaged in listening and acting out the stories. Thus, this study established that using TPR method in teaching short stories enhanced the listening ability of third grade pupils. It is strongly recommended that teacher trainings for Libyan primary school teachers should be intensified and schools should provide appropriate facilities to promote TPR in the classrooms.